Innovative Computing Technology First International Conference, INCT 2011, Tehran, Iran, December 13-15, 2011. Proceedings - Pichappan, Pit.; Ahmadi, Hojat; Ariwa, Ezendu; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the proceedings of the First International Conference on Innovative Computing Technology, INCT 2011, held in Tehran, Iran, in December 2011. The 40 revised papers included in this book were carefully reviewed and selected from 121 submissions. The contributions are organized in topical sections on software; Web services and service architecture; computational intelligence; data modeling; multimedia and image segmentation; natural language processing; networks; cluster computing; and discrete systems.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Information storage and retrieval systems; Artificial intelligence; Computer Science; Information Systems Applications (incl. Internet).; Artificial Intelligence (incl. Robotics).; Software Engineering; Computer Communication Networks; Information Storage and Retrieval; Algorithm Analysis and Problem Complexity